Effects Of High Intensity Interval Training On The Body - Prasetyo, Yona Bayu; Putra, Saddan Pramana; Mandalawati, Titin Kuntum (UNIB Press, 2024)
High-intensity interval training is a form of exercise that involves strenuous activity over a short period of time followed by a recovery period with rest or low-intensity exercise before starting the next workout. AMPK can increase GLUT4 expression through response elements in the bp895 promoter and transcription factors such as guanine nucleotide exchange factor (GEF) and myocyte enhancer factor. This study used the literature review method. Getting 102 journals into 45 journals because through the selection process. The conclusion of this study says that HIIT training can increase muscle oxidation, increase Interleukin-6 (IL-6) levels, and when compared to moderate intensity training, High intensity training is better for weight loss